Analysis of factors related to adolescent role and behavior in preventing transmission: Covid-19 viewed from predisposing, enabling, reinforcing and environmental factors - Tri Anjaswarni; Sri Mugianti; Edy Suyanto; Atti Yudiernawati; Ahmad Zakaria (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Infectious diseases often result in increased morbidity and mortality, as well as during the Corona Virus Disease-19 (Covid-19) pandemic. Children and adolescents are one of the groups at risk for transmission. Transmission of covid-19 in children and adolescents is not too much. This is due to factors related to the behavior of adolescent to prevent the transmission of covid-19. This study aims to analyze factors related to the role and behavior of adolescents in preventing the transmission of covid-19 in terms of predisposing, enabling, reinforcing and environmental factors. The research method is observational with a cross sectional design. The population is adolescents aged 10-21 years in Bareng and Tanjungrejo Sub-Districts, Malang City with a total of 551 people. Samples were taken by simple random technique of 139 respondents. Data analysis used linear regression test. Results: role strengthening factors include predisposing, enabling, reinforcing and the environment significantly influence adolescent behavior in preventing transmission of Covid-19 with a value (P-value) less than 0.05. This shows that all the factors tested are related to the behavior of adolescents to comply in implementing health protocols. The role and behavior of adolescents in preventing infectious diseases needs to be continuously strengthened by various relevant factors so that they can actively participate in preventing its transmission and spread. Abstrak: Penyakit menular sering mengakibatkan meningkatnya angka kesakitan dan kematian, demikian juga pada masa pandemi Corona Virus Desease-19 (Covid-19). Anak dan Remaja adalah salah satu kelompok yang berisiko untuk terjadinya penularan. Penularan covid-19 pada anak dan remaja adalah sedikit. Hal ini disebabkan adanya faktor yang berhubungan dengan perilaku remaja untuk melakukan pencegahan penularan Covid 19. Tujuan penelitian melakukan analisis faktor yang berhubungan dengan peran dan perilaku remaja dalam pencegahan penularan covid-19 ditinjau dari faktor predisposing, enabling (pendukung), reinforcing (pendorong) dan Lingkungan.  Metode penelitian adalah observasional dengan desain cross sectional. Populasi adalah remaja usia 10 - 21 tahun di Kelurahan Bareng dan Tanjungrejo Kota Malang sejumlah 551 orang. Sampel diambil dengan teknik acak sederhana sejumlah 139 responden. Analisis data menggunakan uji regresi linier. Hasil: faktor predisposing, pendukung, pendorong dan lingkungan berpengaruh secara signifikan terhadap perilaku remaja dalam pencegahan penularan Covid-19 dengan nilai (P-value) kurang dari 0,05. Hal ini menunjukkan bahwa semua faktor yang diuji, berhubungan dengan perilaku  remaja untuk patuh dalam mengimplementasikan protokol kesehatan. Peran dan perilaku remaja dalam pencegahan penyakit menular perlu terus menerus dikuatkan dengan berbagai faktor yang relevan agar mereka dapat partisipasi aktif dalam mencegah penularan dan penyebarannya.